SOX9 and SF1 are involved in cyclic AMP-mediated upregulationof anti-Müllerian gene expression in the testicular prepubertal Sertoli cell line SMAT1 - Lasala, Celina (2011)
In Sertoli cells, anti-Müllerian hormone (AMH) expression is upregulated by FSH via cyclic AMP (cAMP), although no classical cAMP response elements exist in the AMH promoter. The response to cAMP involves NF-κB and AP2; however, targeted mutagenesis of their binding sites in the AMH promoter do not completely abolish the response. In this work we assessed whether SOX9, SF1, GATA4, and AP1 might represent alternative pathways involved in cAMP-mediated AMH upregulation, using real-time RTPCR (qPCR), targeted mutagenesis, luciferase assays, and immunocytochemistry in the Sertoli cell line SMAT1. We also explored the signaling cascades potentially involved. In qPCR experiments, Amh, Sox9, Sf1, and Gata4 mRNA levels increased after SMAT1 cells were incubated with cAMP. Blocking PKA abolished the effect of cAMP on Sox9, Sf1, and Gata4 expression, inhibiting PI3K/PKB impaired the effect on Sf1 and Gata4, and reducing MEK1/2 and p38 MAPK activities curtailed Gata4 increase. SOX9 and SF1 translocated to the nucleus after incubation with cAMP. Mutations of the SOX9 or SF1 sites, but not of GAT4 or AP1 sites, precluded the response of a 3,063-bp AMH promoter to cAMP. In conclusion, in the Sertoli cell line SMAT1 cAMP upregulates SOX9, SF1, and GATA4 expression and induces SOX9 and SF1 nuclear translocation mainly through PKA, although other kinases may also participate. SOX9 and SF1 binding to the AMH promoter is essential to increase the activity of the AMH promoter in response to cAMP.